Financing of infrastructure maintenance in South Africa - Ntjatsane, Matsiu Clementinah (My University, 2017)
Infrastructure quality is as important as its quantity, although evidence point to lost growth opportunities due to insufficient investment in maintenance of new and existing infrastructure. Notably, bulk of infrastructure in South Africa is old and collapsing faster than planned and is presently failing to meet increased demand for services. The apartheid government invested heavily in infrastructure development that served only minority of the white population and ignored scarcity of resources that led to high poverty rates in the country. While on the verge of reversing inheritances of the apartheid government, the 1994 democratic government reached out to millions of previously disadvantaged majority population with infrastructure that further improved quality of their lives. However, there was no long-term planning for maintenance; old and new infrastructure received inadequate maintenance and much of it is in a state of disrepair. This research paper aims to explore the condition of the nation’s major economic infrastructure with the intention of discovering the infrastructure gap prevalent to South Africa. It also explores effective financing strategies through which adequate levels of maintenance can be achieved to significantly minimise or close the infrastructure gap. And most importantly discovering capacity constraints for financing infrastructure maintenance and identifying additional sources for securing maintenance funding. Findings of this research indicated that the large infrastructure gap has been a result of maintenance neglect in many areas and inadequacy of maintenance budgets except for infrastructure operated and owned by state owned entities. This study also revealed that South Africa is incapacitated in many aspects which include skills shortage, limited access to financial markets and restrictive regulations governing private sector participation.
A research report submitted to Wits Business School in partial fulfillment of the requirements for the degree of Master of Management in Finance & Investment , March, 2017
Keywords: Infrastructure (Economics); Financial institutions--South Africa